Anchoring Construction Planning in Production - Viklund Tallgren, Mikael (My University, 2016)
With the rising complexity of construction projects, the need to manage this complexity rises. The complexity comes both from the rising amount of subcontractors involved in projects as well as more complex solutions. To mitigate this complexity planning is vital, but as commonly seen in construction projects, few finish on time or on budget. This could in part be identified as a result from the project organisation, where the amount of subcontractors affects the information dissemination and the reliance on the production schedule. Traditionally construction projects employ specialist planners to do the scheduling, this creates distance between workers and the schedule and thus a distrust of the schedule. This leads to the use of the schedule as loose guidelines. In this research one way of countering this has been to include the formen of the contractors in the planning process. By breaking down the project into physical locations and making the participants identify the activities for their contract in each location, the basis of the schedule is anchored and produced collaboratively. By using a collaborative planning session and sequencing of the activities the schedule is anchored. As identified in this research the use of building information models (BIMs), would support this process and help furthering the collective view of the project and help in reducing problems with information filtering through the mixed use of resources such as BIM, drawings and specifications. As it is today planning softwares do not support this kind of scheduling directly from the model. From these described problems a software solution is mapped and a proposed as well as introduced in relation to the planning method.
Keywords: Byggproduktion; Innovation och entreprenörskap (nyttiggörande); Produktion; Building Futures; Construction Management; Innovation & Entrepreneurship; Production; Building Futures